A university crisis provoked by an online class: a communications case study on a social media turbulence - Yago de la Cierva (Taylor & Francis Group, 2021)
In 2020, a Latin American university with a Catholic ethos suffered a crisis when the content of an online class on bioethics regarding homosexuality was posted on Twitter. This communications case study – in which names have been altered to protect confidentiality – describes the objective and subjective circumstances of the case, how the problem evolved, how different stakeholders reacted, and what the University did in order to cope with the crisis. It also narrates what the University did in the post-crisis period to prevent something similar from happening again. The study concludes with a brief analysis of the main takeaways that this case could offer to University authorities and, in general, to managers and communicators in Church-related institutions.